Potential of Plant Essential Oils and Their Components in Animal Agriculture – in vitro Studies on Antibacterial Mode of Action - O’Bryan, Corliss A.; Pendleton, Sean J.; Crandall, Philip G.; Ricke, Steven C. (Frontiers in Veterinary Science, 2015)
The antimicrobial activity of essential oils and their components has been recognized for several years. Essential oils are produced as secondary metabolites by many plants and can be distilled from all different portions of plants. The recent emergence of bacteria resistant to multiple antibiotics has spurred research into the use of essential oils as alternatives. Recent research has demonstrated that many of these essential oils have beneficial effects for livestock, including reduction of foodborne pathogens in these animals. Numerous studies have been made into the mode of action of essential oils, and the resulting elucidation of bacterial cell targets has contributed to new perspectives on countering antimicrobial resistance and pathogenicity of these bacteria. In this review, an overview of the current knowledge about the antibacterial mode of action of essential oils and their constituents is provided.